A Mobile Application for Vegetables Retail Management - Ang, Wan Jie; Samsudin, Noor Azah (Applied Information Technology And Computer Science, 2021)
The uses of smartphones in daily routine are playing a vital role and being widely used in this digital world. The rapid growth of the smartphone has increased the development of mobile applications. This trend became a significant factor for the transformation of the vegetables retail management procedures to be transformed from physical shop to online platform. The traditional way for vegetables retail management procedures is highly time-consuming for transactions of selling vegetables to the customer and causes the difficulties to potential customers to get information about vegetables availability. The purpose of this study is to identify the limitations for the traditional way of vegetables retails management procedure without any mobile-based application and to develop a mobile application to manage vegetables retail management in a more systematic approach in order to resolve the existing problem. A mobile application for vegetables retail management is developed to be used on android-based smartphones. The android studio is used as the integrated development environment (IDE) in Java language with the integration of Firebase as the real-time database for Android development. The prototyping software process model is selected in the system development lifecycle for the development of mobile applications. By developing this mobile application, it allows the user to get access to important information without time-constraints and can purchase the desired vegetables. This technology helps to transform the existing vegetables retails management procedure to an online platform that could be conducted in a more efficient, effective and systematic way.